Chômage et usages de substances psychoactives - Virginie Althaus; Sébastien Ladreyt; Yannick Le Hénaff; Joëlle Mezza; Dominique Lhuilier (Perspectives Interdisciplinaires sur le Travail et la Santé)
There is currently little available research about unemployed workers. The majority of the research on this topic comes from epidemiology and highlights their susceptibility to poor health issues. Here we address the question from the angle of why unemployed workers use psychoactive substance. This study moved therefore from the dominant approach in which substance use is seen as deviant to a non-normative approach. The latter approach allowed us to explore the meaning that these people gave to these uses. In this way, we analysed the individual and collective interviews of 21 unemployed people. Thematic analysis of the interviews highlighted several functions (anaesthetic, stimulation, social) sought by the interviewees. The “anaesthetic” effect or function of psychoactive substances is prevalent in the discourse of the participants and helps them to resist the adverse effects of unemployment.